SCIENCE PROCESS SKILLS DEVELOPMENT : PHOTOSYNTHESIS INGENHOUSZ EXPERIMENTAL LKPD BASED ON PRACTICUM THROUGH LESSON STUDY FOR LEARNING COMMUNITY - Maria Ulfah; Evi Nurhayati; Nanik Widayati; Dewi Nurliyanti; Agung Setyo Nugroho (DIMENSI PENDIDIKAN, 2022)
The research aims to produce Photosynthesis Ingenhousz experimental LKPD based on Science Process Skills through Lesson Study for Learning Community on valid and practical. The Student Worksheet (LKPD) developed is LKPD to facilitate students to have science process skills. The pattern of development of LKPD based on science process skills itself refers to the Lesson Study for Learning Community (LSLC) which consists of planning, implementing, and reflecting. This research method is a Research and Development (R & D) with 4D models (Define, Design, Develop, and Disseminate). Data is collected by using validation sheets. Data analysis was carried out using a quantitative descriptive method on the validity of the LKPD practicum based on Science Process Skills through the Lesson Study for Learning Community. The research results showed that the LKPD practicum based on Science Process Skills through Lesson Study for Learning Community was declared valid with an average score of 3.66. The practicality of LKPD is at criteria 3.60 by teachers and 3.70 by students. Based on the results of the study, it can be concluded that the LKPD practicum based on Science Process Skills through Lesson Study for Learning Community is very valid and practical.